أثر العلاج المعرفي السلوكي في خفض الاكتئاب والقلق والضغط النفسي وتحسين الرفاهية النفسية والثقة بالنفس لمرضى السكري في سلطنة عمان - غداني، ناصر راشد محمد (Kulliyah of Education, International Islamic University Malaysia, 2021)
This study aims for building a cognitive behavioral treatment program to reduce depression, anxiety, and psychological stress, and for improving psychological well-being and self-confidence among diabetic patients in the Sultanate of Oman. The study relied on an experimental approach and a sample of 30 diabetic patients, who were randomly distributed into two equal groups of 15 patients, control group and experimental group. To achieve the study objectives, the researcher built a treatment program based on cognitive behavioral therapy, consisting of 14 treatment sessions. The duration of each session ranges between 60 and 90 minutes, over a period of seven weeks with two treatment sessions per week. The study used the DASS-21 scale, to measure depression, anxiety, and stress, the psychological well-being scale, and the self-confidence scale. The researcher calculated the averages and standard deviations of experimental group's scores for all constructs and dimensions, and on all measurements: pre, post, and follow-up. That is to examine the significance of statistical differences between psychological well-being, self-confidence, depression, anxiety, and stress among members of the experimental group. The researcher used the Lex Lambda test and the samples t-test. At 5% significance level, the results revealed significant differences among the members of the experimental group for the total score of the following measures: psychological well-being, self-confidence, depression, anxiety and stress, and each of their dimensions on the two scales, pre and post, in favor of post-measurement. These are attributed to the effect of the cognitive-behavioral therapy used in this study, which indicates the effectiveness of the treatment program used in this study. The results also showed that there are no significant differences among the members of the experimental group on the total score of the following measures: psychological well-being, self-confidence, depression, anxiety and stress, and each of their dimensions on the two scales: the post and follow-up; which indicates the continuing effectiveness of the cognitive behavioral therapy used in this study